The Impacts of Intellectual Capital on Financial Performance: An Evidence From Indonesian Manufacturing Industry - Josua Tarigan; Stephanie Listijabudhi; S. Elsye Hatane; D. Christine Widjaja (Indonesian Journal of Business and Entrepreneurship (IJBE), 2019)
The purpose of the research was to provide an examination of the impacts of the intellectual capital on the firms' financial performance that is focusing on profitability, productivity, and market value. It was conducted on manufacturing companies in Indonesia which were listed in Indonesian Stock Exchange (IDX). The samples of this research were 93 listed manufacturing companies with the total number of 465 firm-year observations in five years. VAIC method by Pulic was used in measuring the intellectual capital in this research. Based on VAIC approach, intellectual capital consisted of human capital (HCE), structural capital (SCE), and capital employed (CEE). There were ten regression models used to assess all the relationships of independent and dependent variables. The result showed that VAIC had significant relationship towards financial performance but not towards the market value of the companies. While in regards to each component, HCE was found to have no correlation towards both market value and financial performance. The SCE was found to have a negative significant relationship only towards the market value. Meanwhile, CEE was proved to have a significant relationship towards both market value and financial performance.Keywords: intellectual capital, financial performance, market value, VAIC, manufacturing industry